The “deliberative bureaucrat”: deliberative democracy and institutional trust in the jurisdiction of the Finnish planner - Sari Puustinen; Raine Mäntysalo; Jonne Hytönen; Karoliina Jarenko (Routledge, 2022)
The article seeks to elaborate on Forester’s notion of the planner as a “deliberative practitioner”, aiming to add sensitivity to the institutional conditions of planning, focusing especially on Finland. In terms of trust, the concept of deliberative practitioner mostly focuses on interpersonal trust as a planner’s resource in mediating particular interests. Thereby, when applied to the Finnish context, institutional trust may be undermined as a key resource for the Finnish planner’s jurisdiction, justifying his/her proactive role and authority in bringing broader concerns to the planning agenda. This undermining prevents the acknowledgement of important institutional resources that the Finnish planner has in coping with the tensions between communicative ideals and neoliberal realities. A more context-sensitive and institutionally responsive theory of communicative planning is needed to help the planning professionals and other stakeholders conceive the deliberative ideals as supportive for the planners’ institutionally strong agency. Hence, the notion of the “deliberative bureaucrat”. The article seeks to develop an outline for such a theory by drawing upon studies of legal culture, the sociology of professions, deliberative democracy theory and the concept of trust.